Decarbonisation of the power sector to engender a 'Just transition' in Japan: Quantifying local employment impacts. (March 2021) - Kuriyama, Akihisa; Abe, Naoya
Abstract: "Just Transition" is an important, brand new concept to implement policies towards decarbonisation of the power sector in Japan. However, a knowledge gap still remains between this concept and policy discussion at a practical level. Therefore, using the existing scenarios of decarbonisation of the power sector and employment factors for the power sector based on extended input-output tables, this study analysed "Just Transition" issues, looking at the concept from three aspects: distributional justice to identify key impacts by location and economic sector; recognition justice to assess key inequalities; and procedural justice which deal with fair process and possible measures to enhance acceptability of climate policies. The results of this study show that achieving decarbonisation of the power sector provides a net increase in domestic employment and supplies stable jobs in rural areas, thereby contributing to the revitalisation of the local economy. Furthermore, it improves inequalities in the working age population. Support from either national or local government is required to ensure a workforce is in place to enable a rapid increase in renewable energy. To achieve decarbonisation of the power sector with high political acceptability, it is essential to make early decision on the retirement of conventional power plants and to implement policy support for the surplus workers from conventional power plants. Highlights: This study analysed "Just Transition" issues surrounding the decarbonisation of the power sector in Japan using three concepts: distributional justice, recognition justice and procedural justice. Decarbonisation of the power sector contributes to improving the inequality for the working-age population at the regional level. To secure an energy transition with procedural justice, it is essential to take an early decision on the retirement of conventional power plants with policy support for retraining to update expertise of the workers in the power plants.